2013
DOI: 10.1371/journal.pntd.0002508
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Insecticidal Nets Are Synergistic with Mass Drug Administration for Interruption of Lymphatic Filariasis Transmission in Nigeria

Abstract: In central Nigeria Anopheles mosquitoes transmit malaria and lymphatic filariasis (LF). The strategy used for interrupting LF transmission in this area is annual mass drug administration (MDA) with albendazole and ivermectin, but after 8 years of MDA, entomological evaluations in sentinel villages showed continued low-grade mosquito infection rates of 0.32%. After long-lasting insecticidal net (LLIN) distribution by the national malaria program in late 2010, however, we were no longer able to detect infected v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 11 publications
0
23
1
Order By: Relevance
“…The history of the lymphatic filariasis (LF) program in Plateau and Nasarawa states has been published in detail. [11][12][13][14][15] Briefly, it began in 1997 with mapping of seroprevalence of circulating LF antigen in adults. All 30 LGAs were found to be greater than the 1% endemicity threshold (Figure 1), with LGA antigen prevalence ranging from 4% to 62%.…”
Section: History Of the Ivermectin-based Mda Programs In Plateau And mentioning
confidence: 99%
See 1 more Smart Citation
“…The history of the lymphatic filariasis (LF) program in Plateau and Nasarawa states has been published in detail. [11][12][13][14][15] Briefly, it began in 1997 with mapping of seroprevalence of circulating LF antigen in adults. All 30 LGAs were found to be greater than the 1% endemicity threshold (Figure 1), with LGA antigen prevalence ranging from 4% to 62%.…”
Section: History Of the Ivermectin-based Mda Programs In Plateau And mentioning
confidence: 99%
“…12 Various LF evaluations and transmission assessment surveys led to the decision to halt LF MDA in Plateau and Nasarawa states after 2012. [13][14][15] As a result, the 18 non-/hypo-endemic onchocerciasis LGAs received a total of 8-11 rounds of ivermectin-based MDA under the LF program (Table 1). Mass drug administration for onchocerciasis ivermectin monotherapy continued in the 12 meso-hyperendemic onchocerciasis LGAs after the LF MDA program came to its successful conclusion.…”
Section: History Of the Ivermectin-based Mda Programs In Plateau And mentioning
confidence: 99%
“…Yellow fever epidemics have also occurred more recently in central Africa and Brazil and as a result, the WHO have initiated an Eliminating Yellow Fever Epidemic (EYE) strategy with the aim to eliminate such epidemics (WHO, 2017a). Despite such changing biological dynamics, there have been many historical successes in vector control dating back to 1904 including the control of malaria and yellow fever in Panama; malaria in Brazil (with the "eradication" of Anopheles gambiae); onchocerciasis in West Africa; control of dengue in Singapore and Cuba; some initial impact of vector control on Triatome transmission of Chagas' Disease in the Southern Cone of the Americas; filariasis control in the Solomon Islands because of indoor residual spraying (IRS) against malaria vectors (Webber, 1979); and success in filariasis programmes through vector control using bed-nets in Nigeria, The Gambia and Zambia (Blackburn et al 2006;Eigege et al 2013;Rebollo et al 2015;Nsakashalo-Senkwe et al 2017). Perhaps the most notable impact of vector control, however, has been the reduction in malaria morbidity and mortality attributed to long-lasting insecticide-impregnated bed-nets (LLIN) in sub-Saharan Africa.…”
Section: Changing Global Dynamics: a Need For Better Control Of Vectorsmentioning
confidence: 99%
“…The coverage and compliance levels are important to inhibit transmission for a period of 4-6 years, which is the mean reproduction time of adult filarial worms. (6) A study by Karoma et al (7) reported that upon instituting the third MDA round, the program succeeded in reducing the mf rate by 88.5%, from 2.6% to 0.3% and in reducing mean microfilarial density by 17.59 mf/mL, whereas the study by Eigege et al (8) showed that a 90% reduction in mf rate from 3.17% to 0.32% only occurred after implementation of the 8 th MDA round. A systematic review in India identified a coverage-compliance gap in many MDA programs, along with potentially correctable causes.…”
Section: Introductionmentioning
confidence: 99%